Calretinin immunoreactivity in the claustrum of the rat - Druga, Rastislav; Salaj, Martin; Barinka, Filip; Edelstein, Lawrence; Kubová, Hana (Frontiers in Neuroanatomy, 2015)
The claustrum is a telencephalic structure which consists of dorsal segment adjoining the insular cortex and a ventral segment termed also endopiriform nucleus. The dorsal segment (claustrum) is divided into a dorsal and ventral zone, while the endopiriform nucleus is parcellated into dorsal, ventral and intermediate endopiriform nucleus. The claustrum and the endopiriform nucleus consist of glutamatergic projection neurons and GABAergic local interneurons coexpressing calcium binding proteins. Among neurons expressing calcium binding Proteins, the calretinin – immunoreactive interneurons exert specific functions in neuronal circuits, including disinhibition of excitatory neurons. Previous anatomical data indicate extensive and reciprocally organized claustral projections with cerebral cortex. We asked if the distribution of cells immunoreactive for calretinin delineates anatomical or functional subdivisions in the claustrum and in the endopiriform nucleus. Both segments of the claustrum and all subdivisions of the endopiriform nucleus contained calretinin immunoreactive neurons with varying distribution. The ventral zone of the claustrum exhibited weak labeling with isolated cell bodies and thin fibers and is devoid of immunoreactive puncta. Within the medial margin of the intermediate endopiriform nucleus we noted a group of strongly positive neurons. Cells immunoreactive for calretinin in all subdivisions of the claustrum and endopiriform nucleus were bipolar, multipolar and oval with smooth, beaded aspiny dendrites. Small number of calretinin- immunoreactive neurons displayed thin dendrites which enter to adjoining structures. Penetration of dendrites was reciprocal. These results show an inhomogenity over the claustrum and the endopiriform nucleus in distribution and types of calretinin immunoreactive neurons. The distribution of the calretinin – immunoreactive neurons respects the anatomical but not functional zones of the claustral complex.